MADRASAH MANAGERIAL IMPLEMENTATION IN THE LIFE SKILLS PROGRAM TO IMPROVE STUDENT COMPETENCE AT MI BILINGUAL ROUDLOTUL JANNAH PRAMBON SIDOARJO - Doni Samara (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
Principal leadership is a way for someone to influence other people or other groups to want to follow what the leader wants to achieve certain goals. The school principal has an important role in improving the quality of education at MI Roudlotul Jannah. The quality improvement carried out by the Principal of MI Roudlotul Jannah is to produce quality graduates equipped with student life skills. The aims of this research are (1) to describe the role of the principal in shaping the life skills of students at MI Roudlotul Jannah, (2) to find out the forms forms of life skills of students at MI Roudlotul Jannah, (3) to determine the supporting and inhibiting factors for the life skills of students at MI Roudlotul Jannah. The results of this study (1) the leadership role of the principal in shaping the life skills of students at MI Roudlotul Jannah is as a motivator and innovator, and as a guide and director of the life skill program, (2) the forms of life skills of students at MI Roudlotul Jannah who developed are general vocational skills in a particular field. There are many running programs. (3) supporting factors in the formation of students' life skills are adequate facilities and infrastructure, support from parents and the presence of experts in the program. The inhibiting factors are the lack of funds, facilities and infrastructure such as laboratories, lack of enthusiasm from students and clashes with school assignments.